SeLECTS—Self-Limiting Epilepsy with Centrotemporal Spikes: Presence of ESES Correlates with Neuropsychological Regression - Jayakumar, Harish; Padmanabhan, Rama Shankari; Vaikundam, Jayakumar (International Journal of Epilepsy, 2025)
We present a developmentally normal 8-year-old male child with infrequent nocturnal focal seizures since 6 years of age. Since the onset of seizures, he has been having poor academic performance with difficulty in learning and preserved language. Electroencephalogram (EEG) showed a normal background and frequent bisynchronous biphasic centro-parieto-temporal large amplitude spikes with maximum negativity over the left temporal region. His sleep record showed continuous runs of large amplitude generalized spikes with maximum negativity over the centrotemporal region and spike-wave index > 90. There is a clear correlation between the presence of electrical status epilepticus during sleep (ESES) and neuropsychological deficits. EEG is resistant to antiseizure medications, and these findings disappear before mid to late adolescence, and deficits recede with the remission of ESES.
Keywords: BECTS; SeLECTS; CSWS; ESES; benign epilepsy with centrotemporal spikes